2013
DOI: 10.1371/journal.pone.0083550
|View full text |Cite|
|
Sign up to set email alerts
|

Plasticity in Dendroclimatic Response across the Distribution Range of Aleppo Pine (Pinus halepensis)

Abstract: We investigated the variability of the climate-growth relationship of Aleppo pine across its distribution range in the Mediterranean Basin. We constructed a network of tree-ring index chronologies from 63 sites across the region. Correlation function analysis identified the relationships of tree-ring index to climate factors for each site. We also estimated the dominant climatic gradients of the region using principal component analysis of monthly, seasonal, and annual mean temperature and total precipitation … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

12
84
1
4

Year Published

2014
2014
2021
2021

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 107 publications
(101 citation statements)
references
References 86 publications
(91 reference statements)
12
84
1
4
Order By: Relevance
“…4). This result is similar to those reported by de Luis et al (2013), who showed that the growth of Pinus halepensis in drier and warmer regions was more sensitive to mean annual temperature. Our results for F. sylvatica therefore show that trees growing in climatically marginal regions (rather than geographically marginal regions) are more sensitive to climate.…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…4). This result is similar to those reported by de Luis et al (2013), who showed that the growth of Pinus halepensis in drier and warmer regions was more sensitive to mean annual temperature. Our results for F. sylvatica therefore show that trees growing in climatically marginal regions (rather than geographically marginal regions) are more sensitive to climate.…”
Section: Discussionsupporting
confidence: 92%
“…3 and Appendix S6). In summary, significant correlations between RWI and summer temperature (negative) and summer precipitation (positive), both considered indicators of a drought limitation on growth, did not show strong geographical patterns observed in some previous studies (Chen et al 2010;de Luis et al 2013), particularly for summer temperature. This was despite the strong environmental gradients found across our study area (Fig.…”
Section: Geographical Patterns In Growth-climate Relationshipscontrasting
confidence: 62%
See 2 more Smart Citations
“…A similar metric was considered by Levanic et al (2013) in Eastern Europe where the August SPI integrating 3 preceding months was reconstructed. In general, similar responses to late summer precipitation and annual precipitation were detected for other species in the Mediterranean basin (Touchan et al 2007;Martin-Benito et al 2010;de Luis et al 2013).…”
Section: Discussionsupporting
confidence: 58%